Determinan Tingkat Pengangguran di Jawa Tengah - Dwi Laksita Wulandari; Ismadiyanti Purwaning Astuti (Tirtayasa Ekonomika, 2023)
Central Java Province is a region with a large population in Indonesia with 35 regencies/cities, which allows for disparities between regions so that it has the potential to increase the number of unemployed. This study aims to analyze the effect of the short and long-term open unemployment rate in Central Java Province from 2003-2020. The data analysis technique used in this study is the Error Correction Model (ECM) to analyze economic phenomena both in the short and long term. The results of the study in the short-term, inflation and economic growth have a negative and significant effect on the open unemployment rate. In contrast, education has no effect and is insignificant to the unemployment rate. In the long term, economic growth and education negatively and significantly affect the open unemployment rate, while inflation has no effect and is not significant on the available unemployment rate.